Surgical Procedures for Early Colorectal Cancer - Takeshita, Emiko; Tagaya, Nobumi; Yoshiba, Hidemaro; Sameshima, Shinichi; Okuyama, Takashi; Oya, Masatoshi; Sugamata, Yoshitake; Koketsu, Shinichiro (Nippon Daicho Komonbyo Gakkai Zasshi, 2012)
Early colorectal cancer is surgically resected by either local excision or bowel resection. Local excision is principally a method of total biopsy for pathological examination of the lesion. If the lesion is an advanced cancer, or a submucosal cancer having risk factors of lymph node metastasis, additional bowel resection is indicated. Local excision for early colon cancer is rarely performed. Methods of local excision for early rectal cancer include transanal local excision, minimally invasive transanal surgery (MITAS), transanal endoscopic microsurgery (TEM), and transsacral local excision. Both the advantages and disadvantages of each procedure should be well evaluated when selecting the procedure for each lesion. In bowel resection, dissection of regional lymph nodes is usually carried out. For early rectal cancer, pelvic autonomic nerves should be carefully preserved. Intersphincteric resection (ISR) and rectal prolapsing are sometimes used to avoid abdominoperineal excision with permanent colostomy. Laparoscopic surgery is suitable for early colon cancer. Although laparoscopic surgery is currently not yet the standard of care for rectal cancer, its safety and usefulness are being validated by clinical trials because it provides a much better view of the pelvic cavity than conventional open surgery.